2015
DOI: 10.1007/s00248-015-0616-5
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the Diversity of Basidiomycetes from Dead Wood of the Manchurian fir (Abies holophylla) as Evaluated by Fruiting Body Collection, Mycelial Isolation, and 454 Sequencing

Abstract: In this study, three different methods (fruiting body collection, mycelial isolation, and 454 sequencing) were implemented to determine the diversity of wood-inhabiting basidiomycetes from dead Manchurian fir (Abies holophylla). The three methods recovered similar species richness (26 species from fruiting bodies, 32 species from mycelia, and 32 species from 454 sequencing), but Fisher's alpha, Shannon-Wiener, Simpson's diversity indices of fungal communities indicated fruiting body collection and mycelial iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…The low overlap between fungi detected by isolation and those detected by environmental sequencing has been observed previously in wood (Jang et al, 2016) and other substrates (Arnold, Henk, Eells, Lutzoni, & Vilgalys, 2007). We detected 35 wood decay species, 12 by isolation, 24 from direct DNA extracts and only one by both methods.…”
Section: Discussionsupporting
confidence: 67%
“…The low overlap between fungi detected by isolation and those detected by environmental sequencing has been observed previously in wood (Jang et al, 2016) and other substrates (Arnold, Henk, Eells, Lutzoni, & Vilgalys, 2007). We detected 35 wood decay species, 12 by isolation, 24 from direct DNA extracts and only one by both methods.…”
Section: Discussionsupporting
confidence: 67%
“…Jang et al (2015) noted, for example that basidiomycetes detection based on fruiting body collection could be hampered by the ephemeral character of basidiocarps of some species, which due to high water content persist for a short period compared to those of perennial species and thus may not be present at the time of sampling. Another constraint related to this approach may also be the selective medium used for fungal isolation, because, even though benomyl is effective in inhibiting the growth of a large range of fungi other than basidiomycetes, some basidiomycetous species may be sensitive to it and their growth can be inhibited (Jang et al 2015). For macro-fungi revealed by mycelium isolated from infected woody tissues, Taylor (2002) indicated that the number of species of a particular sample is based on the size of the sample, the abundance of species in the sample and the distribution of these species in the substrate where the sample was originally collected.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies have already specifically investigated the mycobiomes of decaying wood using targeted, ampliconbased metagenomics, five in palearctic boreal forests in northern Europe (Ovaskainen et al 2010, Kubartova et al 2012, Ovaskainen et al 2013, Runnel et al 2015 and four in palearctic temperate forests in Europe and Asia (Van der Wal et al 2015, Hoppe et al 2015, Jang et al 2015, Yamashita et al 2015. With the exception of Yamashita et al (2015), which used the V9 region of 18S rDNA, all the other works used the complete ITS (Ovaskainen et al 2010, Kubartova et al 2012, Ovaskainen et al 2013, Hoppe et al 2015, Otosson et al 2015 or the ITS2 (Jang et al 2015, Runnel et al 2015, Van der Wal et al 2015 as the targeted region.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of Yamashita et al (2015), which used the V9 region of 18S rDNA, all the other works used the complete ITS (Ovaskainen et al 2010, Kubartova et al 2012, Ovaskainen et al 2013, Hoppe et al 2015, Otosson et al 2015 or the ITS2 (Jang et al 2015, Runnel et al 2015, Van der Wal et al 2015 as the targeted region. Furthermore, all the analyses of these studies were mainly focused on Basidiomycota, limiting a fully global comparison with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation